2013
DOI: 10.1016/j.jss.2012.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Risk of perforation increases with delay in recognition and surgery for acute appendicitis

Abstract: Background Appendicitis remains a common indication for urgent surgical intervention in the United States, and early appendectomy has long been advocated to mitigate the risk of appendiceal perforation. To better quantify the risk of perforation associated with delayed operative timing, this study examines the impact of length of inpatient stay preceding surgery on rates of perforated appendicitis in both adults and children. Methods This study was a cross-sectional analysis using the National Inpatient Samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
149
2
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(167 citation statements)
references
References 39 publications
5
149
2
11
Order By: Relevance
“…While there is some evidence that delays in diagnosis and treatment make little difference in outcomes, [4][5][6] some studies suggest treatment delays lead to increased rates of perforation, 7 and treatment delayed for more than 36 hours may lead to a perforation rate as high as 65%. 8 To improve diagnostic accuracy, imaging studies have been used with increasing frequency; 9 however, significant limitations such as the ionizing radiation associated with computed tomography (CT) and reduced off-hours availability with ultrasound (US) exist.…”
mentioning
confidence: 99%
“…While there is some evidence that delays in diagnosis and treatment make little difference in outcomes, [4][5][6] some studies suggest treatment delays lead to increased rates of perforation, 7 and treatment delayed for more than 36 hours may lead to a perforation rate as high as 65%. 8 To improve diagnostic accuracy, imaging studies have been used with increasing frequency; 9 however, significant limitations such as the ionizing radiation associated with computed tomography (CT) and reduced off-hours availability with ultrasound (US) exist.…”
mentioning
confidence: 99%
“…9.10 Furthermore the overall rate of complication like sepsis leading to ICU care, urinary and respiratory complications and mortality due to complication was higher in the perforated appendicitis cases. 11,12 CONCLUSION: Incidence of perforated and non-perforated appendicitis in our hospital was 15% and 85% respectively. Incidence of Non-perforated appendices was common in the age group between 30 -40 years.…”
Section: Discussionmentioning
confidence: 75%
“…Delayed surgery usually prolonged the hospital length of stay [10]. There was a 2-fold increase in complication rate for patients delayed longer than 48 hours [11] or greater inpatient delay is associated with increased perforation rates [12]. Some researchers reported that 55 years was the only predictor for perforation or postoperative complications [13].…”
Section: Discussionmentioning
confidence: 99%